Variant course and branching of right brachial artery: a case study - Goswami, Preeti; Tigga, Sarika R.; Bharihoke, Veena (International Journal of Research in Medical Sciences, 2017)
A variant course and branching pattern of the right brachial artery was recorded in a 54-year-old male cadaver during the practical sessions of University College of Medical Sciences, Delhi, India. The right brachial artery divided in the middle third of arm into a medial superficial and lateral deep branch. The superficial medial branch descended anterior to the median nerve and ended by dividing in the cubital fossa into ulnar and radial arteries, whereas the lateral branch descended postero-medial to the median nerve, ending deep to pronator teres as the common interosseous artery. The left brachial artery showed a normal branching pattern by dividing into radial and ulnar arteries in the cubital fossa. The probable origin of such a variation is embryological and familiarity with such variations is imperative as they might affect dynamics of limb function or alter the course of interventional procedures.